Islamic Curriculum Innovation in Integrated Islamic Elementary Schools as an Integrative Approach in Learning Jurisprudence, Akidah, and Tajweed: Inovasi Kurikulum Islam pada Sekolah Dasar Islam Terpadu sebagai Pendekatan Integratif dalam Pembelajaran Fikih, Akidah, dan Tajwid - Rahmawati, Kiki Anita; Ilma, Labibah Sayaka; Rahayu, Indah; Asrohah, Hanun; Zaniyati, Husniyatus Salamah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Integrated Islamic Elementary Schools (SDIT) aim to develop students' religious understanding and character in line with contemporary educational demands. Specific Background: However, the application of curriculum innovation in Islamic subjects—Fiqih, Aqidah, and Tajweed—remains underexplored at the upper-class level. Knowledge Gap: There is limited empirical research on how thematic-integrative approaches are implemented and their impact on student learning outcomes in this context.Aims: This study investigates the implementation of curriculum innovation in Fiqih, Aqidah, and Tajweed learning at SDIT Hidayatul Mubtadiin, Mojokerto Regency. Results: Findings reveal that Fiqih is taught through practical and social projects, Aqidah through reflective-dialogical methods, and Tajweed through digital media and peer teaching. Novelty: The integration of Islamic values into globally and locally relevant themes using a thematical-integrative model enhances contextual religious understanding. Implications: This innovation increases student engagement, comprehension, and character development but faces challenges such as limited digital infrastructure and teacher readiness. The study recommends ongoing teacher training, technology enhancement, and curriculum flexibility to support sustainable innovation in Islamic basic education. Highlights: Thematical-integrative models enhance contextual religious learning. Digital tools and peer teaching boost Tajweed mastery. Innovation faces tech and coordination challenges. Keywords: Curriculum Innovation, Fiqih, Aqidah, Tajweed, Integrated Islamic Education